On the regulation of family and marriage relations in Uzbekistan - X.D. Tillaxodjaeva (Proceedings of The ICECRS, 2019)
This article was prepared on the basis of official statistics and special surveys of families, which were collected and published by the media in Turkestan. In pre-revolutionary Uzbekistan, the principles of family-marriage relations proceeded from the economic relations of the feudal period. Therefore, at this time, the systems of the patriarchal family were characteristic, that is, the dominance of men, the lack of freedom for women, forced marriages, and disregard for the interests and rights of women and children. Today's family customs and traditions have deep historical roots, which were significant precisely at the end of the 19th century on the territory of modern Uzbekistan.